Pandemic Resurrection: Making Gendered Citizenship Visible in a “Postfeminist” Era - Knight Abowitz, Kathleen; Bennett-Kinne, Andrea (Philosophical Inquiry in Education, 2022)
The pandemic resurrected gender as a central categorization of citizenship. COVID-19 reminds us that gender oppression continues in its traditional, materialist formulations to structure our economic, civic, and political lives. Postfeminism has diversified feminist discourses, and at times been used as a temporal claim – the “post” signifying the diminishing need for feminist theory or activism in light of advancements in gender equality. We use postfeminism in a genealogical and critical sense which encompasses the changes in feminisms and enunciates various contradictions that apply to generations of people. The conditions of COVID-19 prompt us to analyze what Stéphanie Genz aptly names boom and bust postfeminism. This analysis generates two implications for philosophers of education working in areas of gender and political identity.